Global risk factors of contrast-induced acute kidney injury: systematic review and meta-analysis. (25th November 2020) - Liu, L; Liu, Y; Chen, S; Chung, E.Y.M; Lei, L; He, Y; Lun, Z; Chen, L; Zhang, H; Zhuang, X; Song, F; Sun, G; et al.
Abstract: Background: Administration of iodinated contrast is common but may be associated with contrast-induced acute kidney injury (CI-AKI), particularly in at-risk patients. There is no recent systematic review of potentially modifiable risk factors. Methods: We searched MEDLINE, Embase and the Cochrane Database of Systematic Reviews (to 30 th June 2019) for observational studies assessing risk factors associated with CI-AKI. Twelve potentially modifiable risk factors were finally included in this thematic review and meta-analysis. Random or fixed meta-analysis was performed to derive the adjusted odds ratio (aOR), and the population attributable risk (PAR) was calculated for each risk factor globally and by region. Findings: We included 157 studies (2, 297, 863 participants). The global incidence of CI-AKI was 5.4%. The potentially modifiable risk factors included high contrast volume (PAR 33%), eight cardiovascular risk factors (diuretic use, multivessel coronary artery disease, acute coronary syndrome, hypertension, hypotension, heart failure, reduced left ventricular ejection fraction and intra-aortic balloon pump use) (combined PAR 76.2%) and three noncardiovascular risk factors (renal dysfunction, diabetes mellitus and anaemia) (combined PAR 47.4%) with geographical differences. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): National Science Foundation of China